A Feasibility Study to Investigate Chemogenetic Modulation of the Locus Coeruleus by Means of Single Unit Activity - Stevens, Latoya (Front Neurosci, 2020)
AIM: Selective chemogenetic modulation of locus coeruleus (LC) neurons would allow dedicated investigation of the role of the LC-NA pathway in brain excitability and disorders such as epilepsy. This study investigated the feasibility of an experimental set-up where chemogenetic modification of the brainstem locus coeruleus NA neurons is aimed at and followed by LC unit activity recording in response to clozapine. METHODS: The LC of male Sprague-Dawley rats was injected with 10 nl of adeno-associated viral vector AAV2/7-PRSx8-hM3Dq-mCherry (n = 19, DREADD group) or AAV2/7-PRSx8-eGFP (n = 13, Controls). Three weeks later, LC unit recordings were performed in anesthetized rats. We investigated whether clozapine, a drug known to bind to modified neurons expressing hM3Dq receptors, was able to increase the LC firing rate. Baseline unit activity was recorded followed by subsequent administration of 0.01 and 0.1 mg/kg of clozapine in all rats. hM3Dq-mcherry expression levels were investigated using immunofluorescence staining of brainstem slices at the end of the experiment. RESULTS: Unit recordings could be performed in 12 rats and in a total of 12 neurons (DREADDs: n = 7, controls: n = 5). Clozapine 0.01 mg/kg did not affect the mean firing rate of recorded LC-neurons; 0.1 mg/kg induced an increased firing rate, irrespective whether neurons were recorded from DREADD or control rats (p = 0.006). Co-labeling of LC neurons and mCherry-tag showed that 20.6 ± 2.3% LC neurons expressed the hM3Dq receptor. Aspecific expression of hM3Dq-mCherry was also observed in non-LC neurons (26.0 ± 4.1%). CONCLUSION: LC unit recording is feasible in an experimental set-up following manipulations for DREADD induction. A relatively low transduction efficiency of the used AAV was found. In view of this finding, the effect of injected clozapine on LC-NA could not be investigated as a reliable outcome parameter for activation of chemogenetically modified LC neurons. The use of AAV2/7, a vector previously applied successfully to target dopaminergic neurons in the substantia nigra, leads to insufficient chemogenetic modification of the LC compared to transduction with AAV2/9.